Communication and religious mission problems - Ningsih, Widia (Islamic Journal of Communication and Public Discourse, 2024)
The purpose of this study is to identify and analyze communication problems faced in religious missions, as well as to formulate recommendations to improve the effectiveness of communication in this context. This research also aims to explore how a more inclusive and adaptive communication approach can help in bridging cultural differences and reducing conflicts that arise in religious missions. Communication problems in religious missions are not only limited to cross-cultural contexts but also occur in internal communication between members of religious organizations. Poor communication can lead to misunderstandings among members, resulting in friction and conflict that is detrimental to the mission as a whole. It is obtained that the implementation of innovative and adaptive communication strategies, religious mission organizations can reach a wider audience and convey religious messages effectively.